Nilai-Nilai Pendidikan Karakter Di Madrasah;Studi Komparatif Atas Nilai Yang Ditanamkan Siswa Madrasah Nu Dan Muhammadiyah - Moh. Nasrul Amin (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
This article describes the character education values ​​that are instilled in NU and Muhammadiyah schools, precisely at MTs Hidayatush Sybyan Cendoro and MTs Muhammadiyah 1 Karangagung. Of course, a school has its own characteristics that make a difference in efforts to instill character values ​​in the madrasa. For this reason, this paper provides the perspective of similarities and differences in character values ​​that are instilled in each school, both NU and Muhammadiyah. The results showed that the internalization of character values ​​carried out by MTs Hidayatush Sybyan Cendoro was 20 character values. The 20 character values ​​consist of 18 character values ​​formulated by the Ministry of National Education, namely religious character, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative, love peace, love to read, care for the environment, care for social, responsibility and 2 values ​​of faith and piety as local values ​​of madrasas. While at MTs Muhammadiyah 1 Karangagung there are 18 character values ​​that refer to the Ministry of National Education in the form of religious character, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative , loves peace, likes to read, cares about the environment, cares about social, responsibility. The similarities in instilling character values ​​into students at MTs Hidayatush Sybyan Cendoro and MTs Muhammadiyah 1 Karangagung are both instilling 18 character values ​​referring to the Ministry of National Education. The difference is that there is an additional character value, namely the value of faith and piety at MTs Hidayatush Sybyan Cendoro called transcendental value which when students are strong in these two values ​​can provide positive encouragement and other character values ​​can be embedded. Meanwhile, at MTs Muhammadiyah 1, religious values ​​are prioritized to be truly embedded in students because they remember the importance of survival